Class IV Lupus Nephritis in the Setting of Serologically Quiescent Disease and Normal Urine Sediment in a Patient with Late-Onset Systemic Lupus Erythematosus - Benedicta Nnodum; Lauren Dudley (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease that may affect any organ of the body. Lupus nephritis (LN) is a frequent and serious complication of SLE. We report a case of an 80-year-old woman who was initially diagnosed with late-onset SLE and eventually developed LN in the setting of normal complements, double-stranded DNA, C-reactive protein, erythrocyte sedimentation rate, and urine sediment. She developed abnormal renal function (creatinine of 1.7 mg/dl) and mild proteinuria (1-2+) without hematuria. Renal biopsy showed class IV lupus glomerulonephritis, active and chronic. The patient was started on mycophenolate mofetil which led to improvement of proteinuria and stabilization of creatinine. The suspicion for LN in a patient with late-onset SLE should remain high when there is development of suspicious renal or urinary abnormalities even if laboratory values do not suggest high disease activity and urinary sediment is normal. To our knowledge, this is one of the oldest patients with biopsy-proven LN and late-onset SLE.